The concept of self generation of electricity by kinetic tile / Anith Athierah Aziz and Asmat Ismail - Aziz, Anith Athierah; Ismail, Asmat (2019)
Nowadays, clean, renewable and environmentally friendly energy generation has always been an issue that needs to be solved. Technologists have created various methods such as solar panels, wind turbine, hydroelectricity and so forth. Harvesting kinetic energies is a sustainable method for generating electricity without depleting natural resources. Furthermore, with the use of Self-Generation of Electricity is an innovative idea, which is to generate electricity from kinetic energy. These tiles use the kinetic energy of a footstep to strain a piezoelectric material. Besides, harvesting electricity these tiles are renewable energy which can light up basic appliances and will contribute to environmental awareness by promoting sustainability and green energy generation.